Evaluation of Door To Needle Time For Fibrinolytic Therapy of ST Elevation Myocardial Infarction (STEMI) Management In Emergency And Traumatology Department (ETD), Hospital Sultan Haji Ahmad Shah (HOSHAS), Temerloh, Pahang. Malaysia. (Bangladesh Journal of Medical Science, 2017)
Introduction: Acute myocardial infarction is known with high mortality. The benefits of fibrinolytic administration in STEMI are time dependent. The purpose of this study is to evaluate the door-to-needle time for fibrinolytic therapy in STEMI patients.Methods: A cross sectional study of all patients who had STEMI was carried out to evaluate the management of STEMI. The duration from door-to-ECG time, door-to-needle time and the factors that contribute to the time frame in receiving treatment was reviewed. The outcomes and complications from fibrinolytic therapy were documented as well. The outcomes of the delayed in administering the treatment were also analyzed in the study.Result: Out of 19 patients received fibrinolytics within 30 minutes, 16 patients (84.2%) had good outcome. In 17 patients received fibrinolytics between 30 minutes to 1 hour, 6 patients (35.2%) had good outcome. In 15 patients received fibrinolytics more than 1 hour, 8 patients (53.3%) had good outcome.Conclusion: This study showed that a shorter door-to-needle time results in better outcome.Bangladesh Journal of Medical Science Vol.16(3) 2017 p.407-412